Re-assessing the Equity Risk Premium - FitzGerald, Adrian (Management School and Economics. The University of Edinburgh, 1997)
Estimates of the historical equity risk premium in the UK are in the range 7 per cent to 9 per cent per annum. Until recently, portfolio investors and industrialists have been encouraged to use a premium of this order in making investment decisions. The purpose of this paper is to review the risk premium debate and to re-inforce the case for rejecting historical experience in formulating future investment plans. A simulation of historical investor expectations suggests that a disciplined appraisal would have identified an average risk premium of less than two per cent per annum. A forward-looking assessment of reasonable expectations suggests that a risk premium assumptions of around 2.5 per cent would be realistic at present.
Keywords: Economics